Are unit export values correct measures of the exports' qualtity? - Krzysztof Szczygielski; Wojciech Grabowski (Center for Social and Economic Research (CASE), 2009)
It has become common to measure the quality of exports using their unit export value (UEV). Applications of this method include studies of intra-industry trade (IIT) and analyses of industrial "competitiveness". This literature seems to assume that export quality and export price (the most natural interpretation of UEV) are not merely correlated but that they follow each other one-for-one. We put this assumption under scrutiny from both a theoretical and empirical point of view. In terms of theory, we formalize this assumption as a hypothesis of the proportionality of equilibrium prices and equilibrium qualities. We discuss several cases for which this hypothesis is theoretically doubtful (non-linear utility- and cost functions; strong and asymmetric horizontal product differentiation). We also suggest two methods of verifying the hypothesis for cases in which it cannot be easily rejected theoretically. These two methods are then applied to German imports in the period of 1994-2006. We find that the implications of the proportionality hypothesis are largely contradicted by the data.
Keywords: F10; F12; F14; 330; export quality; unit export value; intra-industry trade; competitiveness; Produktqualität; Außenhandelspreis; Export; Internationaler Wettbewerb; Intraindustrieller Handel; Außenwirtschaftstheorie; Welt; Deutschland